2018
DOI: 10.3892/etm.2018.6704
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of Bifidobacterium�breve on experimental allergic rhinitis in BALB/c mice

Abstract: Bifidobacterium breve (B. breve) may have a beneficial effect on allergic rhinitis (AR). The aim of the present study was to investigate whether microbial induction of regulatory T cells (Tregs) and adjustment of Th1 and Th2 responses by B. breve are associated with protection against allergic inflammation, and to identify a dose-response association in a murine AR model. Ovalbumin (OVA)-sensitized BALB/c mice were orally treated with different doses of B. breve [1010, 109, 107 and 105 colony forming units (CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
1
17
0
1
Order By: Relevance
“…Oral probiotics can alter the respiratory microbiota and have been advocated as a novel therapeutic strategy for AAD ( 27 ). Our findings are consistent with other reports demonstrating improvement in allergic rhinitis and asthma inflammation through oral administration of Bifidobacterium breve ( 28 ) and Lactobacillus plantarum ( 29 ). However, levels of the main cytokine secreted by Tregs to mediate immune suppression, IL-10, were significantly higher in ATCC 29148 intervention group as compared with the levels in control group.…”
Section: Discussionsupporting
confidence: 93%
“…Oral probiotics can alter the respiratory microbiota and have been advocated as a novel therapeutic strategy for AAD ( 27 ). Our findings are consistent with other reports demonstrating improvement in allergic rhinitis and asthma inflammation through oral administration of Bifidobacterium breve ( 28 ) and Lactobacillus plantarum ( 29 ). However, levels of the main cytokine secreted by Tregs to mediate immune suppression, IL-10, were significantly higher in ATCC 29148 intervention group as compared with the levels in control group.…”
Section: Discussionsupporting
confidence: 93%
“…Kwon et al reported that oral administration of L. sakei WIKIM30 induces tolerogenic DCs and Treg cells, thereby improving allergic symptoms in mouse models of allergic dermatitis (48). It also has been reported that oral administration of Bifidobacterium increases Treg numbers and improves allergic symptoms in OVA-sensitized allergy model mice (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found elevated levels of Bifidobacterium in the nares microbiome during spaceflight. Oral administration of some Bifidobacterium species has been shown to ameliorate allergic rhinitis symptoms in human patients 70 and in a mouse model of allergic rhinitis 71 . Whether the observed increase of Bifidobacterium abundance in the nares may have a similar protective effect on astronauts during spaceflight warrants further investigations.…”
Section: Discussionmentioning
confidence: 99%